Pollinarium morphology of Vincetoxicum (Apocynaceae: Asclepiadoideae) in Turkey - Güven, Seher; Makbul, Serdar; Coskuncelebi Kami̇l; Pinar, Nur Münevver (Phytotaxa, 2015)
In this study, the pollen morphology of 20 representatives of ten taxa of Vincetoxicum from Turkey was observed under a scanning electron microscope and light microscope. Observations showed that each flower contained five pollinaria, including a pair of pollinia and caudicles attached to a central corpusculum. In the investigated taxa, the shape of the pollinium varied from ovate, elliptical, and obovate, to clavate, pollen cell surfaces exhibited gemmate or rugulate ornamentation, and the shape of the corpuscula was ovate or oblong. Numerical analysis showed that the shape of pollinia and corpuscula, size and surface ornamentation of pollen cells, and size of corpuscula and caudicles are valuable traits in delimiting the examined taxa. A key to Turkish Vincetoxicum based on pollinarium morphology is presented.